PENGARUH PEMBERIAN FUNGI MIKORIZA ARBUSKULA DAN PUPUK ORGANIK TERHADAP KANDUNGAN FRAKSI SERAT RUMPUT KUMPAI (Hymenachne amplexicaulis (Rudge) Nees.) PADA ULTISOL - Hardi Syafria; Novirman Jamarun (Udayana University, 2018)
Arbuscular mycorrhizal fungi (FMA) may help the plant for the provision and absorption of P element where as the availability is low in acid soils. Organic fertilizers will affect to the physical, chemical and biological properties of the soil. The purpose of this study was to find out and prove that improvements in ultisol fertility by giving FMA and organic fertilizer will affect the fiber content of kumpai grass. The experiment used a Randomized Block Design with five treatments and 4 replications. The treatments were consisted of: 1) FMA 0 g / pot + organic fertilizer 0%, 2) FMA 20 g / pot + organic fertilizer 50% cow dung, 3) FMA 20 g / po t+ 100% cow manure, 4) FMA 20 g / pot + 50% compost, and 5) FMA 20 g / pot + 100% compost. The observed variables were NDF, ADF, hemicellulose, cellulose and lignin content. The results showed that the treatment had significant effect on all observed variables. Keywords: Hymenache amplexicaulis (Rudge) Nees, fiber fraction, arbuscular mycorrhizal fungi, organicfertilizer